A rare case of schizophrenia coexistence with antiphospholipid syndrome, β-thalassemia, and monoclonal gammopathy of undetermined significance - Jin, Yingming; Cheng, Yiquan; Mi, Jifeng; Xu, Jianfen (Frontiers in Psychiatry, 2023)
A patient with schizophrenia who was treated with chlorpromazine developed lupus anticoagulant (LA) and antiphospholipid syndrome (APS). On protein electrophoresis, a monoclonal immunoglobulin A peak was seen in this patient, defining a condition of monoclonal gammopathy of undetermined significance. Additionally, β-thalassemia was diagnosed with the CD41-42 genotype. This condition is extremely rare, particularly in patients with schizophrenia and APS. We present a case of a patient with schizophrenia and secondary APS who had a positive LA, a significantly prolonged activated partial thromboplastin time, endogenous coagulation factor deficiency and inhibitor, no bleeding, and an unexpected finding of β-thalassemia and monoclonal IgA. Following that, a literature review on the patient was presented.